The Effect of Empowerment and Teamwork on Affective Commitment and Management Performance from the Aspects of Benefits and Impact on Producer Cooperatives in Pekanbaru City - Anggraini, Winda; Machasin, Machasin; Garnasih, Raden Lestari (CV. Rayyan Dwi Bharata, 2024)
This research aims to find out whether Empowerment and Teamwork influence Affective Commitment in Producer Cooperatives in Pekanbaru City. To find out whether Empowerment and Teamwork influence the Performance of Management in Producer Cooperatives in Pekanbaru City. To find out Affective Commitment influences the Performance of Management in Producer Cooperatives in Pekanbaru City. To find out whether Empowerment has an effect on Management Performance through Affective Commitment in Producer Cooperatives in Pekanbaru City. To find out how teamwork influences management performance through affective commitment in producer cooperatives in Pekanbaru City. Hypothesis testing uses the Smart-PLS test tool. The data analysis method uses Path Analysis. The results of the research are that Empowerment and Teamwork have a significant effect on Affective Commitment and Management Performance. Affective Commitment has a significant influence on Management Performance. Indirectly, Empowerment through Affective Commitment has a significant influence on Management Performance, and indirectly Teamwork through Affective Commitment has a significant influence on Management Performance.